Alimentación infantil y desempeño escolar en estudiantes de la IEPSM N°6010148 Balbina Dora Soto Correa, Caballococha 2024 - Salas Tapullima, Nazario Tercero (2024)
The study aimed to explore the relationship between child nutrition and academic performance among students at IEPSM N° 6010148 Balbina Dora Soto Correa in Caballococha during the year 2024. A non-experimental, cross-sectional, field based, bivariate, and relational research design was employed. The sample consisted of 191 students selected through a census sampling method. Surveys and questionnaires were used for data collection. Statistical results revealed a significant relationship between child nutrition and academic performance, with a p-value of .003, which is below the established significance level of .05. This led to the acceptance of the alternative hypothesis and the rejection of the null hypothesis. The correlation coefficient (rho = .213) demonstrated a positive relationship between the analyzed variables, indicating that adequate nutrition is associated with better academic performance among students during the studied period.